Numerical simulation of explosive welded titanium and Al7075-T6 bimetal composite plate using ANSYS Autodyn. (3rd August 2022) - Barua, Abhishek; Jeet, Siddharth; Kumari, Kanchan; Bagal, Dilip Kumar; Pradhan, Swastik
Abstract: The aim of this paper is to use the smoothed particle hydrodynamics (SPH) technique (in Ansys Autodyn), to create a more physically realistic 2 D numerical model for the simulation of explosive welding of Titanium with Aluminum alloy Al7075-T6. The flyer plate was made of titanium, while the base plate was made of Al7075-T6. The Al7075-T6 plate served as the foundation for the majority of the jet's components. The majority of the jet's components were built on top of the Al7075-T6 plate. The jet flew at a speed of 1100 m/s, as anticipated by the model. In addition, the pressure at the explosion site was insufficient to bind the two plates. As a result, a unique tiny region of plastic strain formed at the impact zone. Despite the fact that the two plates were facing opposite directions, there were no signs of shear forces between them. Due to severe plastic deformation and localised melting of the parent plates, the interface shape changed from straight to wavelike as the detonation wave moved across it during the simulation. Both alloys behave like fluids, resulting in the formation of a wavy morphology with vortices, which is in good agreement with the previous studies.